1970
DOI: 10.3758/bf03331876
|View full text |Cite
|
Sign up to set email alerts
|

Secondary self-punitive behavior: Effects of periodic punishment of Sidman avoidance by a Pavlovian CS+

Abstract: Seven naive rats were trained on Sidman avoidance. Following adaptation to 3-sec response-contingent light presentations, Ss reeeived alternate days of VI 3-sec classical conditioning in which the light was paired with shock. During testing, the unreinforced light es was response produced during short periods of the avoidance sessions. Acceleration of avoidance ("secondary" self-punitive behavior) resulted during these periods, Pavlovian extinction resulted in its rapid attenuation, and Pavlovian reconditionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1972
1972
1978
1978

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Hineline (1966) found that allowing the animals to avoid by lever holding instead of by repeated pressing produced some reduction in the warmup, but did not eliminate it entirely. On the other hand, Reiss and his colleagues have carried out several experiments with a free-operant shuttle response, finding very quick acquisition, and virtually no warm-up effects (e.g., Martin & Riess, 1969 ;Riess, 1970). Riess and Farrar (1972) documented these features with detailed data.…”
mentioning
confidence: 99%
“…Hineline (1966) found that allowing the animals to avoid by lever holding instead of by repeated pressing produced some reduction in the warmup, but did not eliminate it entirely. On the other hand, Reiss and his colleagues have carried out several experiments with a free-operant shuttle response, finding very quick acquisition, and virtually no warm-up effects (e.g., Martin & Riess, 1969 ;Riess, 1970). Riess and Farrar (1972) documented these features with detailed data.…”
mentioning
confidence: 99%